Selection and phenotypic stability of M4 mutants of pearl millet (Pennisetum glaucum (L.) R. Br.) derived from gamma rays induced mutagenesis in Niger - Mounkaila Boureim Mouhamadoua; Daouda Ousmane Sani; Issa Yacouba Abdoul-Bachir; Sani Daouda Abdoul Razak; Mahamadou Adamou Nassirou; Lawali Mamane Nassourou; Soumaila Sounakoye Illiassa (European Scientific Journal, ESJ, 2024)
Gamma irradiation mutagenesis is an approach that offers a wide range of possibilities for varietal selection.  In the simultaneous induction of multiple mutations to modify several plant traits. The aim of the present study was to select seed lots for four mutants of the M4 generation. An experiment was carried out in an experimental plot to purify drought-tolerant M4 genotypes based on morphological characteristics. Potential mutants MI 02/82, MI 13/63, MI 12/72, and MI 10/54 were tested in a randomized complete block design. The parameters measured were: the number of tillers, stem height, number of internodes, number and length of ears, stem and spike diameters, and cycle duration. A dendrogram was first generated to identify the homogenous subgroups. Then an analysis of variance ANOVA was conducted between individuals of the same subgroups to evaluate the variance. On morphological parameters, results showed that MI 13/63 and MI 10/54 genotypes have a homogeneous population from M4 onwards. MI 12/72 can be classified into two different subgroups according to ear length. MI 02/82, on the other hand, showed a high degree of variability at M4. These results will contribute to the selected new varieties adapted to the needs of rural producers in order to improve the productivity of pearl millet in Niger.